KRUKENBERG TUMOR IN OVARY- A CASE REPORT - DR. MANISH KUMAR NIGAM M.D (International Journal of Pharma and Bio Sciences, 2013)
Krukenberg tumor is a metastatic signet ring cell adenocarcinoma of the ovary. It is uncommon, accounting for 1% to 2% of all ovarian tumors, most commonly observed in the stomach-ovarian axis. Here a case of Krukenberg berg tumor is presenting whose primary site was from breast.